Ours to explore privilege, power, and the paradox of voluntourism - Biddle, Pippa (Potomac Books, an imprint of the University of Nebraska Press, 2021)
Ours to Explore investigates voluntourism's past and present, uncovering the complicated roots of the modern global phenomenon.